Pengembangan Sistem Informasi Pelayanan Kesehatan Berbasis Web Pada Klinik Pratama Universitas Pahlawan - Nainggolan, Priya Octavia Nainggolan; Saide; Safni Marwa (Universitas Pahlawan Tuanku Tambusai, 2024)
Pratama UP Clinic is a health service institution that provides services based on promotive, preventive, curative, and rehabilitative implementation. Services are also provided in the form of outpatient, inpatient, 1-day service and home care. This study aims to develop a web-based health service information system at the Pratama Universitas Pahlawan Clinic. The manual system used previously was considered less efficient in managing patient data, medical records, pharmacists, and cashiers. Likewise, the initial development system that has been designed is still less efficient, such as in medical records that are not in accordance with the Pratama UP Clinic, then there are deficiencies in the poly field, and there is service data in the system that is inaccurate or contains service prices in the system. Therefore, a new, more complex system was developed using the PHP programming language with the Laravel framework and MySQL database. This system includes various features such as Emergency Unit Poly (UGD), Baby SPA, medical records, drug management by pharmacists, and payment by cashiers. The development of this web-based system uses the Prototype method, which allows for repeated evaluation and improvement until the system meets user needs. This system testing uses the Black Box Testing method which shows that all features on the system function or run properly. Keywords: Information System, Primary Clinic, PHP, Prototype, Black box testing.